Konstrukce přípravku pro chirurgické zavádění osseointegračních implantátů u obličejových epitéz - Koukal, Ondřej (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2012)
Cílem této bakalářské práce je návrh a konstrukce přípravku pro chirurgické zavedení osseointegračních implantátů pro upevnění epitézy oblasti orbitu. Jako podklad pro konstrukční práci byla dodána data z CT pacienta. Dále práce obsahuje rešerši na téma využití osseointegrace při zavádění obličejových epitéz.

The aim of this bachelor thesis is the design and contstruction of a preparation for surgical introduction of osseointegration implant, of which function is fixing an epithesis in the orbit area. Computer Tomography data of a patient was provided as a basis for design work. The thesis also includes a research on osseointegration utilization in the introduction of facial epithesis.
Design of the surgical preparation for facial implant osseointegration
Keywords: osseointegrace; obličejové epitézy; Reverse Engeneering; Rapid Prototyping; osseointegration; facial epithesis; Reverse Engeneering; Rapid Prototyping